Persepsi Mahasiswa Akuntansi Reguler dan Non Reguler Universitas Udayana Terhadap Minat Mengikuti Pendidikan Profesi Akuntansi - Dewi, Ida Ayu Riana Puspita; Sari, Maria Mediatrix Ratna (E-Jurnal Akuntansi; Vol 25 No 3 (2018)DO - 10.24843/EJA.2018.v25.i03.p23, 2018)
Accounting Profession Education is an advanced education in the field of accounting profession. This study aims to find out the perception of Udayana University's regular and irregular accounting students to follow Accounting Profession Education as measured by career motivation, quality motivation, social motivation, and education cost. Determination of sample using non probability sampling method with purposive sampling technique. The number of respondents were 78 people who calculated using Slovin formula. Methods of data collection conducted survey method with questionnaire technique measured using Likert scale. Data analysis technique used is multiple linear regression analysis. This study obtained the result that the higher the motivation of career, quality motivation, and social motivation, the greater the interest of regular and irregular accounting students Udayana University followed Professional Accounting Education, while the cost of education does not affect the interests of regular and non regular accounting students Udayana University Accounting Profession. Keywords: motivation, interest, accounting profession education.